Significant Changes of Tourism Industry in the Altai-Sayan Mountainous Region - DUNETS, Aleksandr N.; ZHOGOVA, Inna G. (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018DO - 10.14505//jemt.9.4(28).21, 2018)
This paper considers the significant changes that have occurred in the tourist space of the Altai-Sayan mountainous region. In fact, it is a cross-border area and an important tourist region in the Russian Federation. It should be mentioned that the structure of the tourist space can be studied properly while using the model of the territorial tourist system. The authors examine the common features of tourism systems in the mountainous environments of the region. The study examines the tourist infrastructure, organizers of tourist services, local people’s attitudes and tourists’ preferences in the tourist industry. Studies in the field of tourist space enable to distinguish the types of tourism and their distribution in the Altai-Sayan region. It is worthwhile noting that health tourism  has become one of the fastest  growing  subfields in the tourist industry of this region. The tourist development projects such as the economic zone of “Turquoise Katun” and shore development projects of warm lakes have also encouraged this process. Moreover, ecotourism development is of great importance to this area because there are many protected natural areas and some of them are under UNESCO  protection. Also, tourism development outlooks are associated with cross-border cooperation and sustainable economic development of the region.